The use of BCAA to decrease delayed-onset muscle soreness after a single bout of exercise: a systematic review and meta-analysis - Weber, Martim Gomes; Dias, Silas Seolin; de Angelis, Tarlyson Regioli; Fernandes, Eduardo Vignoto; Bernardes, Andrea Gomes; Milanez, Vinicius Flavio; Jussiani, Eduardo Inocente; de Paula Ramos, Solange (Amino acids, 2021)
Branched-chain amino acids (BCAA) are used as a recovery method after exercise-induced muscle damage (EIMD). Although data suggest that BCAA may alleviate the delayed-onset muscle soreness (DOMS) evoked by EIMD, there is no consensus about the most effective supplementation protocol. To investigate the effects of BCAA on DOMS after a single exercise session that caused EIMD, a systematic review and meta-analysis were conducted on the effectiveness of BCAA supplementation to reduce DOMS symptoms in healthy subjects after a single session of EIMD. Randomized clinical trials (RCT) were searched in Medline, Cochrane Library, Science Direct, SciELO, LILACS, SciVerse Scopus, Springer Link journals, Wiley Online Library, and Scholar Google, until May 2021. Ten RCTs were included in the systematic review and nine in the meta-analysis. Seven studies demonstrated that BCAA reduced DOMS after 24 to 72 h. BCAA doses of up to 255 mg/kg/day, or in trained subjects, for mild to moderate EIMD, could blunt DOMS symptoms. However, high variability between studies due to training status, different doses, time of treatment, and severity of EIMD do not allow us to conclude whether BCAA supplementation is efficient in untrained subjects, applied acutely or during a period of pre to post days of EIMD, and at higher doses (> 255 mg/kg/day). The overall effects of BCAA on DOMS after a single session of exercise were considered useful for improving muscle recovery by reducing DOMS in trained subjects, at low doses, in mild to moderate EIMD, and should not be administered only after the EIMD protocol.